Juncture interview: Gillian Tett. Issue 1 (7th June 2013) - Tett, Gillian
Abstract : Award‐winning financial journalistGillian Tett joins IPPR director and Juncture co‐editor Nick Pearce to discuss the crisis of faith at the root of the financial crash, the disaster of austerity, the great expectations of new Bank of England governor Mark Carney, and the state of economic thinking in post‐crash Britain.